An integrated study on the comprehensive mechanism of Schisandra chinensis polysaccharides mitigating Alzheimer's disease in rats using a UPLC-Q-TOF-MS based serum and urine metabolomics strategy. Issue 2 (23rd December 2022) - Fu, Jun; Li, Jixun; Sun, Yuzhen; Liu, Shu; Song, Fengrui; Liu, Zhongying
Abstract : Therapeutic effects and potential mechanism of action of homogeneous polysaccharide SCP2 on AD rats. Abstract : As a well-known traditional Chinese medicine and functional food, Schisandra chinensis ( S. chinensis ) has been proved to possess excellent neuroprotective effects, and particularly the role of the polysaccharide fraction in neuroprotection has been increasingly emphasized. The aim of this study was to investigate the therapeutic effects and potential mechanism of action of the homogeneous polysaccharide SCP2, isolated and purified from S. chinensis polysaccharide (SCP), on Alzheimer's disease (AD) rats based on a holistic metabolomics approach in serum and urine. The results of the pharmacodynamics study showed that SCP2 significantly improved Aβ25–35 -induced cognitive dysfunction, improved oxidative damage and reduced Aβ deposition in the hippocampus. The holistic metabolomics results of serum and urine showed that the intervention with SCP2 significantly reversed the metabolic profile disorder in AD rats. A total of 40 metabolites (21 serum metabolites and 19 urine metabolites) were identified, which were mainly involved in linoleic acid metabolism, alpha-linolenic acid metabolism and arachidonic acid metabolism. The results obtained in this study will provide new insights into the mechanisms of SCP2 in the treatment of AD and provide a basis for the subsequent structure–activity studies of SCP2.